Challenge of building information modelling (BIM) implementation in Malaysia AEC industry - Muhammad Khairul Anuar, Isa (2019)
Building information Modelling (BIM) is an advanced concept for the majority of companies operating in AEC industry. BIM provide a new paradigm to design, construct, operate and maintain a facility. However, even with the dedicated use, stakeholders can go through into troubles during its implementation on a project or within an organization. The AEC industry in Malaysia is very compelling and the implementation of new technological advancements and construction systems has been a major concern for the stakeholders. Therefore, the study aims to identify the elements challenging of implementation of BIM in Malaysian AEC industry. Thirty-five challenges with BIM implementation were identified and most of the factors could be correlated with the organization unit. The data has been managed through designed questionnaires and the prioritization of such factors is relied upon to help the main stakeholders to address the issues as per their need which will spare parcel of time and financial with implementation if BIM in Malaysian AEC industry